Pain Sensitivity and Pain Catastrophizing are Associated with Persistent Pain and Disability after Lumbar Spine Surgery - Coronado, Rogelio A. (Arch Phys Med Rehabil, 2015)
OBJECTIVE: To examine whether pain sensitivity and pain catastrophizing are associated with persistent pain and disability after lumbar spine surgery. DESIGN: Prospective observational cohort study. SETTING: Academic medical center. PARTICIPANTS: Patients (N = 68, mean ± SD age = 57.9 ± 13.1 years, N female = 40 (58.8%)) undergoing spine surgery for a degenerative condition from March 1, 2012 to April 30, 2013 were assessed 6 weeks, 3 months, and 6 months after surgery. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURE(S): The main outcome measures were persistent back pain intensity, pain interference, and disability. Patients with persistent back pain intensity, pain interference, or disability were identified as those patients reporting Brief Pain Inventory scores ≥ 4 and Oswestry Disability Index scores ≥ 21 at all postoperative time points. RESULTS: From 6 weeks to 6 months after surgery, approximately 12.9%, 24.2%, and 46.8% of patients reported persistent back pain intensity, pain interference, or disability, respectively. Increased pain sensitivity at 6 weeks was associated with having persistent back pain intensity (OR = 2.0, 95% CI = 1.0; 4.1) after surgery. Increased pain catastrophizing at 6 weeks was associated with having persistent back pain intensity (OR = 1.1, 95% CI = 1.0; 1.2), pain interference (OR = 1.1, 95% CI = 1.0; 1.2), and disability (OR = 1.3, 95% CI = 1.1; 1.4). An interaction effect was not found between pain sensitivity and pain catastrophizing on persistent outcomes (p > 0.05). CONCLUSION(S): Findings suggest the importance of early postoperative screening for pain sensitivity and pain catastrophizing in order to identify patients at-risk for poor postoperative pain intensity, interference, and/or disability outcomes. Future research should consider the benefit of targeted therapeutic strategies for patients with these postoperative prognostic factors.